Pengaruh Fasilitas Belajar dan Kompetensi Guru IPS Terhadap Prestasi Belajar Siswa pada Mata Pelajaran IPS Terpadu Kelas VIII MTsN 6 Tulungagung - Arel Vaganza; Jani Jani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Education is the main foundation in forming quality Human Resources. In achieving educational goals, support is needed from various aspects, including the availability of adequate learning facilities and competent teachers. Learning facilities play an important role in supporting the learning process, while teacher competence greatly determines the success of transferring knowledge to students. These two aspects are believed to have an influence on student learning achievement, including in Integrated Social Studies subjects that require conceptual understanding and critical thinking skills. This research was conducted to answer three main questions: (1) whether there is an influence of learning facilities on student learning achievement in Integrated Social Studies subjects grade VIII MTsN 6 Tulungagun; (2) whether the competence of social studies teachers affects student learning achievement in Integrated Social Studies subjects grade VIII MTsN 6 Tulungagun; and (3) how much influence the two variables simultaneously have on student learning achievement in the Integrated Social Studies subject class VIII MTsN 6 Tulungagun. The purpose of this study is to analyze and prove the influence of each independent variable on the bound variable both partially and simultaneously. This study uses a quantitative approach with an associative method. The population is 309 students of grade VIII MTsN 6 Tulungagung and the sample is 76 students taken using the Simple Random Sampling technique, and 3 social studies teachers of Class VIII as additional informants. The data collection technique was carried out through questionnaires for independent variables and documentation of UAS values for bound variables. Data analysis was carried out using validity, reliability, normality, multiple linear regression tests, as well as t-tests, F tests and R2 tests with the help of JASP software. The results of this study after processing data using the t-test showed that neither learning facilities nor the competence of social studies teachers had a significant effect on student learning achievement, because the significance value of learning facilities was above 0.05. However, the results of the F test showed that simultaneously the two variables had a significant effect on student learning outcomes with a significance value of <0.001. In addition, the determination coefficient value (R2) of 0.179 showed that 17.9% of the variation in student learning achievement was influenced by learning facilities and the competence of social studies teachers together. These findings show the importance of synergy between the quality of educational facilities and the competence of teaching staff in supporting student learning outcomes.